2019
DOI: 10.3389/fped.2019.00482
|View full text |Cite
|
Sign up to set email alerts
|

FOXG1 Dose in Brain Development

Abstract: Brain development is a highly regulated process that involves the precise spatio-temporal activation of cell signaling cues. Transcription factors play an integral role in this process by relaying information from external signaling cues to the genome. The transcription factor Forkhead box G1 (FOXG1) is expressed in the developing nervous system with a critical role in forebrain development. Altered dosage of FOXG1 due to deletions, duplications, or functional gain- or loss-of-function mutations, leads to a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 126 publications
(161 reference statements)
0
49
0
Order By: Relevance
“…Another described function of AKT is the regulation of the FOXG1 transcriptional repressor (Datta et al, 1999;Regad et al, 2007;Dastidar et al, 2011). FOXG1 plays crucial roles in early brain development, and loss of FOXG1 leads to microcephaly, developmental delay, and cerebral atrophy (Hettige and Ernst, 2019). Studies by Baek et al (2015) showed that expression of the Akt E17K variant by IUE altered AKT-FOXG1 signaling in mice, resulting in increased reelin expression during development.…”
Section: Differential Activation Of Intracellular Pathways In Mtoropathiesmentioning
confidence: 99%
“…Another described function of AKT is the regulation of the FOXG1 transcriptional repressor (Datta et al, 1999;Regad et al, 2007;Dastidar et al, 2011). FOXG1 plays crucial roles in early brain development, and loss of FOXG1 leads to microcephaly, developmental delay, and cerebral atrophy (Hettige and Ernst, 2019). Studies by Baek et al (2015) showed that expression of the Akt E17K variant by IUE altered AKT-FOXG1 signaling in mice, resulting in increased reelin expression during development.…”
Section: Differential Activation Of Intracellular Pathways In Mtoropathiesmentioning
confidence: 99%
“…Mechanistically, FOXG1 interacts with the global transcriptional corepressors of the Groucho/transducing-like Enhancer of the split (TLE) family suggesting that FOXG1 acts as a transcriptional repressor coordinating the control of neural progenitor cell proliferation with the timing of differentiation (Yao et al , 2000). Disruption in FOXG1 in humans leads to structural brain abnormalities including microcephaly and agenesis of the corpus callosum (Shoichet et al , 2005; Kortum et al ., 2011; Hettige & Ernst, 2019). In addition, human mutations in both FOXP1 and FOXP2 lead to severe speech and cognitive impairments (Lai et al , 2000; MacDermot et al ., 2005; Takahashi et al , 2009; Horn et al , 2010; Nudel & Newbury, 2013; Han et al ., 2019); where both genes have also been linked to autism spectrum disorders (Takahashi et al ., 2009; Mukamel et al , 2011; Bowers & Konopka, 2012b, a).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high degree of conservation identity in the DNA-binding domain, Fox proteins bind different target sequences with great specificity, effecting regulation of the transcription of large array of genes directing major developmental processes such as cell proliferation and cell fate specification (Clark et al ., 1993; Carlsson & Mahlapuu, 2002; Lehmann et al , 2003; Nakagawa et al , 2013). Human genetic analyses have shown several FOX genes have important biological functions associated with brain development; these include FOXG1 (potential determinant of forebrain size; Florian et al , 2012; Hettige & Ernst, 2019; Pringsheim et al , 2019) and FOXP2 (vocal learning; MacDermot et al , 2005; Fisher & Scharff, 2009; Nudel & Newbury, 2013). Further, mutations in FOXG1, FOXC2, FOXL2, FOXP1 and FOXP2 have profound effects on human brain development including microcephaly, intellectual impairments, and language disorders (D’Haene et al , 2010; Kortum et al , 2011; Butler et al , 2012; Seltzer & Paciorkowski, 2014; Han et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…With the extension of development time, the expression area of FoxG1 changes. At mouse E12.5, FoxG1 is still expressed in the NPCs of the telencephalon, but no longer expressed in other neural tubes ( Hettige and Ernst, 2019 ). In the mature mouse brain, FoxG1 is only expressed in neuroepithelial cells such as the cerebral cortex and hippocampus ( Hettige and Ernst, 2019 ).…”
Section: The Role Of Foxg1 In the Neural Stem Cellsmentioning
confidence: 99%
“…At mouse E12.5, FoxG1 is still expressed in the NPCs of the telencephalon, but no longer expressed in other neural tubes ( Hettige and Ernst, 2019 ). In the mature mouse brain, FoxG1 is only expressed in neuroepithelial cells such as the cerebral cortex and hippocampus ( Hettige and Ernst, 2019 ). These indicate that FoxG1 can regulate the telencephalic development through spatio-temporal patterning and interaction with different signaling.…”
Section: The Role Of Foxg1 In the Neural Stem Cellsmentioning
confidence: 99%